Comparison of Depression, Anxiety and Stress in Caregivers of Patients with Schizophrenia and Bipolar Affective Disorder - Ain, Qurat ul; Mansoor, Sawera; Zubair, Usama Bin; Abbas, Nadeem; Latif, Tooba; Baqir, Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare depression, anxiety, and stress amongst caregivers of patients with Schizophrenia and Bipolar Affective Disorder Study Design: Cross-sectional study. Place and Duration of Study: Psychiatry Department, Fauji Foundation Hospital, Rawalpindi Pakistan, from May to Nov 2021 Methodology: One hundred caregivers of patients with Schizophrenia and Bipolar Affective Disorder took part in the study. The “Depression Anxiety Stress Scales” scale assessed depression, anxiety and stress. The difference in both groups was checked by the chi-square test. Results: One hundred caregivers (46 caregivers of patients with Schizophrenia and 54 caregivers of patients with the bipolar affective disorder) were recruited. Among caregivers of patients with Schizophrenia, 29(63%) had significant depression, 33(71%) had anxiety, and an equal proportion had stress. Of those who cared for patients with bipolar affective disorder,16(29.6 %) had depression, 29(53.7 %) had anxiety, and 25(46.29%) had stress. Depression, anxiety, and stress among caregivers had a statistically significant association with clinical diagnosis in our target population (p-valve 0.002, 0.033, 0.007), respectively. Conclusion: Depression, anxiety, and stress are significantly higher among caregivers of patients with Schizophrenia as compared to caregivers of patients with bipolar affective disorder. Our findings have identified a significant need for supporting caregivers of patients with serious mental illness.